Design of Delivery Drone and the Interaction : A Public User Perspective - Lingam, S.N.; Verstegen, R.; Petermeijer, S.M.; Martens, M. (ACM, 2024)
Drones will likely enter public spaces soon for deliveries, interacting with humans as recipients or bystanders. Understanding their requirements and factors contributing to uncertainty is crucial for safer Human-Drone Interaction design. Twelve participants were interviewed and engaged in focus groups. Preliminary results indicate the need for clear communication of drone intentions through design and interfaces, guiding future research and design concepts to be tested with user studies for delivery drones in public spaces.